2019
DOI: 10.1038/s41598-019-49622-y
|View full text |Cite
|
Sign up to set email alerts
|

Stable fabrication of a large nanopore by controlled dielectric breakdown in a high-pH solution for the detection of various-sized molecules

Abstract: For nanopore sensing of various-sized molecules with high sensitivity, the size of the nanopore should be adjusted according to the size of each target molecule. For solid-state nanopores, a simple and inexpensive nanopore fabrication method utilizing dielectric breakdown of a membrane is widely used. This method is suitable for fabricating a small nanopore. However, it suffers two serious problems when attempting to fabricate a large nanopore: the generation of multiple nanopores and the non-opening failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…In contrast, the operational range of CDB is mostly limited to <40 nm, while laser‐assisted CDB could reach diameters around ∼50 nm [50]. Studies with larger diameter pores (in the ∼40 nm range) are seldom reported [49,51] and are mostly done in the <30 nm diameter range [3,52]. To produce larger diameter pores through CDB, a higher voltage must be applied.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the operational range of CDB is mostly limited to <40 nm, while laser‐assisted CDB could reach diameters around ∼50 nm [50]. Studies with larger diameter pores (in the ∼40 nm range) are seldom reported [49,51] and are mostly done in the <30 nm diameter range [3,52]. To produce larger diameter pores through CDB, a higher voltage must be applied.…”
Section: Resultsmentioning
confidence: 99%
“…77,78 Making such tailormade nanopores is possible by TEM drilling, 72,79 or even by dielectric breakdown of the membrane. 35,80 Prior simulations and experimental studies have shown the ability to detect dsDNA molecules using ultra-thin 2D materials, 18 with certain shortcomings, like higher basepair velocity (hBN nanopores) 53 or undesirable hydrophobic interactions causing pore clogging 48 (graphene). Using molecular dynamics, we were able to show that our proposed Gr+hBN structure was able to overcome these main drawbacks by demonstrating their ability to have distinguishable dwell times and ionic currents.…”
Section: Resultsmentioning
confidence: 99%
“…133,134 Interestingly, these thinned regions demonstrated non-negligible transmembrane conductance (tens of nanosiemens) but could be distinguished from nanopores due to significant rectification in the measured current. 133,134 Unfortunately, it is not clear whether such thinned regions are a widespread phenomena that have remained undetected in other studies, or are specific to the experimental conditions used in these works. It is noted that for SiN x films thicker than 10 nm, the effective length of the nanopore fabricated via CBD has been reported to be approximately one third of the membrane thickness.…”
Section: Challenges Of Controlled Breakdownmentioning
confidence: 99%
“…Performing CBD in a high pH solution (pH 4 12) can also create nanopores rather than thinned regions in the membrane. 134 However, in general the best results in the literature (in terms of consistency of creating nanopores of a desired diameter) have been obtained at pH 8-10. 124 Lastly, CBD can result in irregularly shaped nanopores [ Fig.…”
Section: Challenges Of Controlled Breakdownmentioning
confidence: 99%